Field evidence for the lateral emplacement of igneous dykes: Implications for 3D mechanical models and the plumbing beneath fissure eruptions - Healy, David; Rizzo, Roberto E; Duffy, Marcus; Farrell, Natalie J C; Hole, Michael J; Muirhead, David (Volcanica, 2018)
Seismological and geodetic data from modern volcanic systems strongly suggest that magma is transported significant distance (tens of kilometres) in the subsurface away from central volcanic vents. Geological evidence for lateral emplacement preserved within exposed dykes includes aligned fabrics of vesicles and phenocrysts, striations on wall rocks and the anisotropy of magnetic susceptibility. In this paper, we present geometrical evidence for the lateral emplacement of segmented dykes restricted to a narrow depth range in the crust. Near-total exposure of three dykes on wave cut platforms around Birsay (Orkney, UK) are used to map out floor and roof contacts of neighbouring dyke segments in relay zones. The field evidence suggests emplacement from the WSW towards the ENE, and that the dykes are segmented over their entire vertical extent. Geometrical evidence for the lateral emplacement of segmented dykes is likely more robust than inferences drawn from flow-related fabrics, due to the prevalence of ubiquitous ‘drainback’ events (i.e. magmatic flow reversals) observed in modern systems.